Drug interactions and possible serotonin syndrome in a patient with fibromyalgia - MASTROIANNI, Patricia de Carvalho; VARALLO, Fabiana Rossi; MACHUCA, Manuel (Vitae, 2014)
Depression associated with fibromyalgia can be treated with selective serotonin reuptake inhibitors (SSRI) as fluoxetine, paroxetine or citalopram; or with serotonin–norepinephrine reuptake inhibitors (duloxetine or milnacipran). In patients with fibromyalgia, several meta-analyses have demonstrated the effectiveness of antidepressants, particularly the tricyclic antidepressant (TCA) amitriptyline, which reduce the pain, fatigue, depression, and sleep disturbances. Additionally, tramadol, pregabalin, and gabapentin are other treatment options.